The Sustainability of Palm Oil - Dhenada, Mohd Ikbal Mohd Huda; Huda, Mohd Ikbal Mohd (Environmental Management and Sustainable Development, 2024)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The most significant environmental issue associated with palm oil that is accused by the European Union is deforestation, particularly in Indonesia and Malaysia. The tension arose after the EU established Renewable Energy Directive II. EU considered palm oil-producing countries have ignored environmental issues by expanding palm oil plantations which has resulted in deforestation. This made palm oil plantations included in the high-risk Indirect Land Use Change (ILUC) category. Therefore, this article presents a comparison of the sustainability between palm oil and other vegetable oils such as sunflower oil, rapeseed oil, etc<strong style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">. <span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The findings of this article contextualize the comparative advantage of palm oil over other similar resources. The reasons why palm oil is more sustainable are it needs less land to produce the same amount of oil, its sustainability certification at the international level such as RSPO which is also connected to SDGs, and at the domestic level such as ISPO and MSPO. One strategy proposed in this article is instead of boycotting palm oil, the government and stakeholders should prioritize the implementation of sustainable practices, enhance the monitoring and enforcement of RSPO scheme standards, and tackle social concerns and deforestation that are always linked to palm oil.